2020
DOI: 10.3390/en13215553
|View full text |Cite
|
Sign up to set email alerts
|

Application of Industry 4.0 to the Product Development Process in Project-Type Production

Abstract: Currently, the concept of Industry 4.0 (I4.0) is reaching most companies by changing the characteristics of their production systems. The aim of this study was to determine the possibilities of applying I4.0 concepts and tools to the product development process in a small- to medium-sized enterprise (SME)—a food processing technology supplier that offers individually tailored solutions. The study employs the case study methodology along with conceptual studies. Based on the available I4.0 concepts/technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 106 publications
(111 reference statements)
1
9
0
Order By: Relevance
“…Which confirms the statement that the pandemic under certain conditions accelerated the development of companies in the field of implementing IT innovations (Baryshnikova et al, 2021). Additionally, it can be suggested that companies providing financial services are preparing for much larger changes that are coming with the new principles of sustainability management, Industry 4.0 or Industry 5.0 (Aspiranti et al, 2020;Iden et al, 2020;Ingaldi and Ulewicz, 2020;Lazar et al, 2021;Pietraszek et al, 2020;Urban et al, 2020).…”
supporting
confidence: 68%
“…Which confirms the statement that the pandemic under certain conditions accelerated the development of companies in the field of implementing IT innovations (Baryshnikova et al, 2021). Additionally, it can be suggested that companies providing financial services are preparing for much larger changes that are coming with the new principles of sustainability management, Industry 4.0 or Industry 5.0 (Aspiranti et al, 2020;Iden et al, 2020;Ingaldi and Ulewicz, 2020;Lazar et al, 2021;Pietraszek et al, 2020;Urban et al, 2020).…”
supporting
confidence: 68%
“…As indicated by Norton et al [20] and Banwo and Du [24], there is a lack of research linking intrinsic employee motivation, organizational culture, and proenvironmental practices in the workplace. The literature on energy conservation in manufacturing primarily focuses on manufacturing technologies [34,35] and energy efficiency processes [36,37], and less on the roles of employees in developing green workplace practices. To address this research gap, our study examines the roles of organizational culture in promoting green behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation uses different computer tools and technologies to imitate real manufacturing operations, systems, processes, product design, and factory layout to create virtual testing models and prototypes before converting them to reality (Dalmarco et al 2019 ; Moktadir et al 2018 ; Urban et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%